2014
DOI: 10.1007/s00259-013-2441-8
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT assessment in follicular lymphoma using standardized criteria: central review in the PRIMA study

Abstract: We confirm that FDG PET/CT status when applying the 5PS with a cut-off ≥4 is strongly predictive of outcome after first-line immunochemotherapy for FL. Further efforts to refine the criteria for assessing minimal residual FDG uptake in FL should provide a reproducible platform for response assessment in future prospective studies of a PET-adapted approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…[34][35][36][37][38][39][40][41] There was, however, no association between baseline SUV max and either PFS or response, in agreement with the results of another recent study in FL. [31] SUV is derived from a single measurement in Table 3. Impact on PFS of percentage change in SUV, MTV, and TLG between baseline and EOI treatment using optimal cutoff values.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41] There was, however, no association between baseline SUV max and either PFS or response, in agreement with the results of another recent study in FL. [31] SUV is derived from a single measurement in Table 3. Impact on PFS of percentage change in SUV, MTV, and TLG between baseline and EOI treatment using optimal cutoff values.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive number of studies have shown that FDG-PET performed post-treatment is highly predictive of PFS and OS with and without residual masses on CT. The vast number of studies in aggressive NHL has been summarized in a systematic review [63], while the data on indolent NHL are based on fewer studies [64][65][66]. Based on these findings, the International Harmonization Project developed new recommendations for response criteria for aggressive malignant lymphomas, incorporating FDG-PET into the definitions of end-of-treatment response in FDG-avid lymphomas [67,68].…”
Section: Pet/ct For Post-therapy Response Evaluation Of Lymphomasmentioning
confidence: 99%
“…These studies suggested that using the hepatic FDG activity, as a reference cut-off for PET positivity in HL, is better than using the mediastinal blood pool [19]. Recently, TychyjPinel et al [20] has shown that PET positivity determined using the IHP criteria failed to predict progression. However, PET positivity determined using the Deauville 5-point scale (with a cut-off of C4) did predict progression, with 3.5-year PET-positive and PET-negative PFS of 25.0 and 61.4 %, respectively.…”
Section: Discussionmentioning
confidence: 97%